2009
DOI: 10.1007/s11064-009-0087-5
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition of Frontal, Temporal and Parietal Neocortex in the Normal Human Brain and in Alzheimer’s Disease

Abstract: Dietary omega3-polyunsaturated fatty acids are thought to influence the risk of Alzheimer's disease (AD), and supplemental docosahexaenoic acid (DHA; 22:6n-3) has been reported to reduce neurodegeneration in mouse models of AD. We have analysed the fatty acid composition of frontal, temporal and parietal neocortex in 58 normal and 114 AD brains. Significant reductions were found for stearic acid (18:0) in frontal and temporal cortex and arachidonic acid (20:4n-6) in temporal cortex in AD, and increases in olei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
95
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(107 citation statements)
references
References 36 publications
11
95
1
Order By: Relevance
“…While plaques and tangles are hallmarks of the disease, other apparently unrelated laboratory abnormali-ties are routinely detected in patients, including elevated cholesterol [4], altered fatty acid [5,6], glucose [7,8], and phospholipid [9] metabolism, aberrant calcium homeostasis [10], and mitochondrial dysfunction [11]. These features of AD have received far less attention because of the lack of direct links to the amyloid cascade, and have engendered numerous competing hypotheses to explain the pathogenesis of AD.…”
mentioning
confidence: 99%
“…While plaques and tangles are hallmarks of the disease, other apparently unrelated laboratory abnormali-ties are routinely detected in patients, including elevated cholesterol [4], altered fatty acid [5,6], glucose [7,8], and phospholipid [9] metabolism, aberrant calcium homeostasis [10], and mitochondrial dysfunction [11]. These features of AD have received far less attention because of the lack of direct links to the amyloid cascade, and have engendered numerous competing hypotheses to explain the pathogenesis of AD.…”
mentioning
confidence: 99%
“…However, there are reports showing that PUFAs do not change significantly in the AD brain compared to the healthy brain [108] . In addition, overexpression of Fat-1, enhancing endogenous production of n-3 PUFAs, in 3×Tg-AD mice significantly reduces phosphorylated tau and improves brain function [106] .…”
Section: Role Of Fatty-acid Metabolism In Ad Pathogenesismentioning
confidence: 89%
“…In contrast, arachidonic acid increases Aβ production and the formation of amyloid plaques and other neuropathology [91] . Some studies have confirmed the animal results and shown decreased levels of PUFAs and MUFAs in the AD brain [107] .However, there are reports showing that PUFAs do not change significantly in the AD brain compared to the healthy brain [108] . In addition, overexpression of Fat-1, enhancing endogenous production of n-3 PUFAs, in 3×Tg-AD mice significantly reduces phosphorylated tau and improves brain function [106] .…”
mentioning
confidence: 79%
“…Both C22:6n-3 and C20:4n-6 remained unchanged in HF, as well as the total n-3 and total n-6 PUFAs. C22:6n-3 and C20:4n-6 are the main fatty acids in the medial basal hypothalamus of cows (67), and the main fatty acids in major neural systems in humans (68,69). We hypothesise increased C20:5n-3 and C20:3n-6, followed by unchanged C22:6n-3 and C20:4n-6 in HF hypothalamus is the result of a protective mechanism in which peripheral tissues supply these fatty acids, as evidenced by their reduced levels in peripheral tissues.…”
Section: We Did Not Find Any Differences In Hypothalamic Levels Of Irmentioning
confidence: 99%